Market power, growth, and wealth inequality - Giammario Impullitti; Pontus Rendahl (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2025)
In recent decades, the United States has experienced a notable rise in markups, a slowdown in productivity growth, and an increase in wealth inequality. We present a framework that unifies these trends into a common driving force. In particular, increased barriers to entry raise markups and boost corporate profits. Rising profits elevates firm valuations, fuels the demand for capital, and drives up asset returns. At the same time, the reduction in competition stifles overall economic growth. Wealth inequality is shaped by the return gap, r - g, which represents the difference between asset returns and the economy's growth rate. The rise in capital demand together with a reduction in growth leads to a widening of the return gap, which amplifies inequality by affecting the saving patterns of households in different ways across the wealth distribution, deepening the divide between the rich and the poor. These trends result in substantial welfare losses for the majority of households, while only the top 1%, and especially the top 0:1%, experience gains.
Keywords: 330; Market Power; Growth; Heterogeneous Agents; Wealth Distribution